Influence of COVID-19 on Social Networks of Non-competitive Events in School and Adult Ages? A Case Study - Gamonales, José M. (2022)
Social networks are useful and effective as a tool for improving sporting events. Therefore, the aim of the present study was to analyze the statistical data of participation and impact of social media (Facebook, Twitter, and Instagram) of the Gymnastics of Extremadura, and to know the influence of Covid-19 pandemic on them. For this, the participation and interaction data on social networks were analyzed, between the periods 2016-2017, 2017-2018, 2018-2019, and 2019-2020. The same marketing strategy was always used in all online media. A descriptive and exploratory analysis of the data was performed. The results showed that the number of participants in the event has increased significantly since the use of social networks, with women being the main followers. Facebook is the social medium mainly used by users to get to know the Gymnastics of Extremadura. Therefore, the results demonstrate the importance of knowing the interactions of followers on social media to plan new online marketing strategies. Also, despite the event being suspended, as a consequence of the Covid-19 pandemic, the statistical data of the event's social networks are increasing every year. Being, the moment of publication of the poster or suspension of the event, the instants that receive the greatest number of actions in social networks such as Like or Share / Retweet the news.